2003
DOI: 10.1590/s0021-75572003000600008
|View full text |Cite
|
Sign up to set email alerts
|

Incentivo ao aleitamento materno: a importância do pediatra com treinamento específico

Abstract: In this study, a pediatrician who was prepared and motivated to encourage breastfeeding performed similarly to a multiprofessional breastfeeding team in terms of promoting exclusive breastfeeding until 4 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
12
0
9
Order By: Relevance
“…In the same study when comparing the two groups, the preterm infants showed a higher percentage of early weaning than the late preterm for both factors. Study points out the educational causes of early weaning, being poor handling the most prominent 22 . Study shows that 17.8% of the mothers responded as cause of weaning the weak milk and 14.7% that the milk dried up 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study when comparing the two groups, the preterm infants showed a higher percentage of early weaning than the late preterm for both factors. Study points out the educational causes of early weaning, being poor handling the most prominent 22 . Study shows that 17.8% of the mothers responded as cause of weaning the weak milk and 14.7% that the milk dried up 23 .…”
Section: Resultsmentioning
confidence: 99%
“…The SGA infants have a higher risk of neonatal death than those who did not show signs of intrauterine growth delay 22 . Late premature with fetal growth restriction showed a greater time of stay in the ICU and neonatal complications than appropriate for gestational age (AGA) 17 .…”
mentioning
confidence: 93%
“…For better understanding of this reality, we need to check pediatricians' knowledge about breastfeeding. The fact that pediatricians in child care have training in breastfeeding is positively associated with breastfeeding (26) . According to a study conducted in Australia, it is important to know about the experiences of women concerning the advices received from health professionals, in order to know if there is consistency in the recommendations (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudos prévios mostram que, embora esses profissionais possuam informações sobre as vantagens do AM, eles não dispõem de informações para manejo das principais dificuldades enfrentadas pelas nutrizes como ingurgitamentos, técnica inadequada, ou problemas com os mamilos. Como constatado em estudos anteriores 3 , um profissional de saúde com treinamento específico, altamente motivado para o incentivo ao AM pode obter melhoras no índice de AM de uma população 23,24 .…”
Section: Aspectos éTicosunclassified